(untitled) (Ameghiniana, 2013)
The general morphology and the cuticle of a new Bennettitalean frond, Ptillophyllum ghiense n. sp. are described in the present paper. This species has been found in presumably Lower Cretaceous strata near the locality Paso Roballos, Santa Cruz Province. It is the first concrete record of this taphoflora.